Political Struggle for the Renewal of the Ottoman Empire - Permana, Indra Martian; Putra, Rulian Haryadi; Munandar, Asep Nur Imam (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
The aim of this research is to analyze the relationship between nationalism and historical awareness. The method used in this study employs a literature review with specific steps. The findings of this research indicate that the downfall of the Ottoman Empire is the result of complex dynamics, involving the roles of intellectuals, government policies, the paradox of reforms, poor political language, and the influence of the Young Turks movement. From the era of Mahmud II to the collapse of the absolute rule of the Sultan, the shift in the foundational values of the state from Islam to nationalist identity reflects the challenges of a transformation that was not always successful. The incompatibility between reformists and the majority of the Muslim population, particularly in the political communication of the Sultan, becomes a key factor complicating the achievement of consensus. This research provides profound insights into the complexity of the history of the Ottoman Empire, emphasizing the importance of comprehensively understanding social, cultural, and political aspects in analyzing the decline of an empire. Consequently, a more comprehensive understanding of these events can offer valuable lessons in detailing and comprehending the dynamics that shape historical changes.